Sistema de información geográfico de procesos y datos de temáticos de obras del programa de recuperación de la infraestuctura afectada por las inundaciones 2008 - 2009, realizado por Corpecuador Delegación Machala - Abril Rodas, Cristhian Mauricio (2010)
Currently aerial photography and satellite imagery specifications have allowed analysis and constant observation of phenomena occurring on the earth, making it possible to achieve a mapping of this information by developing new tools.